HEXALOCK BRICK : INOVASI BATAKO PENDUKUNG KONSEP PRE- FEBRICATE BUILDING YANG RINGAN, EKONOMIS DAN RAMAH LINGKUNGAN - Nugroho, Samsu Adi; Fadilah, Muhammad Dikri; Ginting, Thesalonika Br; Nurdiana, Asri (Jurnal Proyek Teknik Sipil, 2019)
The construction material innovation that will be discussed in thispublication is a lightweight brick with the HexaLock Brick model. This brick was ismade from cement, sand, and stryrofoam waste. The concept used in this brick is alock system with a hexagonal design that is more stable than ordinary brick shapes.From the results of the tests that have been done, it was found that HexaLock Brickhas several advantages compared to ordinary brick, which are lighter, more efficientfiller, smaller water absorption, smaller thermal resistance, and faster constructiontime.